DNA methylation alterations caused by Leishmania infection may generate a microenvironment prone to tumour development - Vega-Benedetti, Ana Florencia; Loi, Eleonora; Zavattari, Patrizia (Frontiers in Cellular and Infection Microbiology, 2022)
DNA methylation is an epigenetic signature consisting of a methyl group at the 5’ cytosine of CpG dinucleotides. Modifications in DNA methylation pattern have been detected in cancer and infectious diseases and may be associated with gene expression changes. In cancer development DNA methylation aberrations are early events whereas in infectious diseases these epigenetic changes may be due to host / pathogen interaction. In particular, in leishmaniasis, a parasitic disease caused by the protozoan Leishmania, DNA methylation alterations have been detected in macrophages upon infection with Leishmania donovani and in skin lesions from patients with cutaneous leishmaniasis. Interestingly, different types of cancers, such as cutaneous malignant lesions, lymphoma and hepatocellular carcinoma, have been diagnosed in patients with a history of leishmaniasis. In fact, it is known that there exists an association between cancer and infectious diseases. Leishmania infection may increase susceptibility to develop cancer but the mechanisms involved are not entirely clear. Considering these aspects, in this review we discuss the hypothesis that DNA methylation alterations induced by Leishmania may trigger tumorigenesis in long term infection since these epigenetic modifications may enhance and accumulate during chronic leishmaniasis.